Primulina campanuloides, a new cave-dwelling species of Gesneriaceae from central Guangxi, China - Qin, Shao-Yu; Fu, Jia-Xin; Chou, Wei-Chuen; Fu, Long-Fei; Wei, Yi-Gang (Phytotaxa, 2026)
A new species of Gesneriaceae from Mashan County, Guangxi Zhuang Autonomous Region, China, Primulina campanuloides Shao Y.Qin, W.C.Chou & F.Wen, was described and illustrated. It is morphologically similar to P. longzhouensis B.Pan & W.H.Wu, but can be readily distinguished from the latter by several key characteristics: leaves nearly spatulate to narrowly obovate (vs. leaves elliptic or broadly elliptic to suborbicular), cymes unbranched or 1-branched, usually 2–8 flowered (vs. cymes usually 2–3-branched, 5–25 flowered), corolla tube inflated below (vs. corolla tube cylindrical) and pistil exserted (vs. pistil included). Supporting evidence includes field photographs depicting its flowering ecology and detailed descriptions of its distribution. Currently, we found only one population, approximately 800 individuals, at the type locality. Based on the criteria established by the International Union for Conservation of Nature (IUCN), the conservation status of P. campanuloides is preliminarily assessed as Vulnerable [VU D1+2].